Beyond Dominance and Competence: A Moral Virtue Theory of Status Attainment. (August 2017) - Bai, Feng
Recognition has grown that moral behavior (e.g., generosity) plays a role in status attainment, yet it remains unclear how, why, and when demonstrating moral characteristics enhances status. Drawing on philosophy, anthropology, psychology, and organizational behavior, I critically review a third route to attaining status: virtue, and propose a moral virtue theory of status attainment to provide a generalized account of the role of morality in status attainment. The moral virtue theory posits that acts of virtue elicit feelings of warmth and admiration (for virtue), and willing deference, toward the virtuous actor. I further consider how the scope and priority of moralities and virtues endorsed by a moral community are bound by culture and social class to affect which moral characteristics enhance status. I end by outlining an agenda for future research into the role of virtue in status attainment.